Organic Amines as Targeting Stabilizer at the Polymer/Fullerene Interface for Polymer:PC61BM Solar Cells. Issue 12 (12th May 2020) - Li, Zerui; Yan, Lingpeng; Shan, Jiankai; Gu, Huimin; Lin, Yi; Wang, Yaling; Tan, Hongwei; Ma, Chang-Qi
Abstract : Herein, it is demonstrated that a small amount (0.05% in weight ratio) of polyethyleneimine (PEI) can effectively suppress the "burn‐in" degradation of both PTB7‐Th:PC61 BM and P3HT:PC61 BM cells, similar to the piperazine derivatives, suggesting that organic amines can serve as universal stabilizer in polymer:PC61 BM solar cells. Light‐induced electron spin resonance (LESR) spectroscopy measurement shows a higher ESR signal intensity of PC61 BM anions in 0.2% PEI‐doped film than in 1% piperazine‐doped film. Moreover, no piperazine is detected in a 10% (w/w) piperazine‐doped film by gas chromatography–mass spectrometry (GSMS). These results suggest that the residual piperazine in the blend film is very low, which can be understood by the high volatility of piperazine. Quantum calculations are performed on the intermolecular binding energy ( E B ) between polymer (using model repeating units), PC61 BM, and piperazine molecules. Results reveal that piperazine prefers to localize at the polymer:fullerene interface by complexing with PC61 BM (in P3HT:PC61 BM) or PTB7‐Th (in PTB7‐Th:PC61 BM system), which indicates that the photo dimerization of PC61 BM which causes the "burn‐in" degradation of polymer:fullerene solar cells mainly happens at the donor/acceptor interface, and the organic amine serves as the targeting stabilizer at the interface. Abstract : All NH containing organic amines can serve as the targeting stabilizers in polymer:fullerene solar cells, which mainly localize at the interface of the polymer/PC61 BM crystalline domains. Furthermore, only a small amount of amine is enough for suppressing the formation of fullerene triplet and PCBM dimerization under illumination, thus improving the device stability.